Profits of Products Processed from Bamboos of the Forest Area of Mareje Bonga, Central Lombok, Indonesia - Husnuzzonni, Husnuzzonni; Sjah, Taslim; Yanuartati, Baiq Yulfia Elsadewi (PT FORMOSA CENDEKIA GLOBAL, 2025)
The aim of this research is to analyze the profits generated from products processed from bamboo sourced from the Forest Area of Mareje Bonga, Central Lombok, Indonesia. It is expected to bring several benefits, particularly to improve the livelihood of the communities inside and outside the area of the forest. This research used a survey method. The surveys were carried out with semi-structured interviews and field observation to bamboo locations, bamboo growers, bamboo processors, and bamboo traders. These primary data were completed with secondary data. Collected data were analyzed accordingly by applying several analyses, such as descriptive analysis, descriptive statistics, and profit. The study revealed that bamboos from the area of Mareje Bonga Forest are marketed inside and outside the area. The bamboos are then processed into several bamboo products of high and low added values or profits. Inside the area of the forest, a higher profit was generated by large buckets. Outside the forest area, three bamboo products were promising for their profits, i.e., gazebo, set bench, and lazy bench. There are more types of bamboo products and more profitable bamboo products outside the forest area than inside. The novelty of this study is on the finding that more profitable products are located at a longer distance from its resources. This study brings several implications in economics, environment, and policy making.